2012
DOI: 10.1097/inf.0b013e3182463879
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procalcitonin Value is Useful for Predicting Severity of Kawasaki Disease

Abstract: We measured serum procalcitonin concentrations in 160 patients suffering from Kawasaki disease. Serum procalcitonin was significantly higher in nonresponders to an initial intravenous immunoglobulin treatment than in responders. A cutoff value of procalcitonin (0.5 ng/mL) for nonresponders showed that the sensitivity was 85% and the accuracy was 64%. Multivariate logistic regression analysis revealed that procalcitonin-positive cases showed the highest risk for nonresponders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 1 publication
3
18
0
Order By: Relevance
“…However, more nonresponders than responders had a PCT level >1.0 ng/mL, and there was a significant difference in PCT between responders and nonresponders in the KD group after adjustment for age by using ANCOVA. Another study investigating responders and nonresponders to initial IVIG treatment demonstrated that PCT levels were significantly higher in nonresponders than in responders10). This result was similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, more nonresponders than responders had a PCT level >1.0 ng/mL, and there was a significant difference in PCT between responders and nonresponders in the KD group after adjustment for age by using ANCOVA. Another study investigating responders and nonresponders to initial IVIG treatment demonstrated that PCT levels were significantly higher in nonresponders than in responders10). This result was similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 92%
“…Although the clinical impact of serum PCT levels in patients with KD has not been determined, the relation between PCT and KD severity, and the comparison of PCT levels between complete and incomplete KD were also reported1011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have observed that non‐infectious triggers, such as surgical trauma , burns, Kawasaki disease , and adult onset Still's disease can induce PCT elevation . In HSCT recipients, donor leukocytes might result in PCT elevation.…”
Section: Discussionmentioning
confidence: 99%
“…IVIGR poses great harm to KD patients, and early identification and adoption of more aggressive treatment measures can effectively reduce vascular complications and improve prognoses. A cluster of risk factors for IVIGRKD have been reported in the past decade including elevated total bilirubin and aspartate transaminase [ 10 ], PCT > 0.5 ng/ml [ 11 ], band count > 10%, albumin ≤ 30 g/L and abnormal first echocardiographic results [ 12 ], elevated neutrophil ratio and alanine aminotransferase, low albumin (< 29 g/L) and pericardial effusion [ 13 ], elevated total bilirubin and C-reactive protein [ 14 ], gallbladder effusion and cholecystitis [ 15 ], C-reactive protein ≥ 10 mg/dL, lactate dehydrogenase ≥ 590 IU/L and hemoglobin ≥ 110 g/L [ 16 ]. Previous studies added to our understanding of IVIGRKD and also raised the demand on how to accurately predict its occurrence.…”
Section: Discussionmentioning
confidence: 99%